Peningkatan Keunggulan Bersaing melalui Supply Chain Flexibility beserta Variabel Antecentnta pada Industri Manufaktur di Jawa Timur - Ubud, Sahnaz (Universitas Brawijaya, Indonesia, 2009)
The objective of this research is to explore the relationship between environmental uncertainly, supply chain flexibility and competitive advantage. The population in this research are all of manufacturing industrial with the big scale in east java. The population have been registered in industrial & trading department (DEPERINDAG) and have used internet to support the supply chain process. So the population are 204 firms. Proportional area random sampling was used to analyze the relationship between environmental uncertainly, supply chain flexibility and competitive advantage. The research has found a positive direct relation between environmental uncertainly and supply chain flexibility, and positive direct relation between supply chain flexibility and competitive advantage. Beside that the research has found a positive indirect relation between environmental uncertainly and competitive advantage through supply chain flexibility. Finally, the results indicate that ability of firm for anticipate environmental uncertainty can enhance competitive advantage if that factors are related to supply chain flexibility.